1982
DOI: 10.1007/bf02373703
|View full text |Cite
|
Sign up to set email alerts
|

Mineral N effects on cowpea and soybean crops in a Nigerian soil

Abstract: SummaryThe amounts of N fixed in the field in Nigeria by four cowpea and two soybean cultivars were determined at different levels of available N by the difference and the "AN'-value methods using non-nodulating soybean, maize and celosia as non-fixing controls. No significant differences were found between the two methods or with different controls. Grain removal and return of residues to the soil were measured and net soil-N changes calculated. N-benefits accrued from two of the cowpea cultivars when grown a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
1

Year Published

1986
1986
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 8 publications
1
20
0
1
Order By: Relevance
“…Because some studies on N fertilization did not concurrently quantify N 2 fixation and other studies did not evaluate response to N fertilizer when quantifying N 2 fixation, data analyses were performed for two data sub-sets: Data set A was used to examine relationships between N uptake, N 2 fixation and grain yield; Data set B was used to evaluate yield response to fertilizer-N. Data set A comprised 61 studies in which N 2 fixation was quantified. Several different techniques were used: (1) the N difference method (Dashti et al, 1998, Israel and Burton, 1997, Israel and Mikkelsen, 2001, Saxena and Chandel, 1997, Thies et al, 1995, Wagner and Zapata, 1982, Weber, 1966; (2) Ureides determination in the xylem sap (Gan et al, 2002, Guafa et al, 1993, Herridge, 1982, Herridge et al, 1990, Hughes and Herridge, 1989, Hungria et al, 2003, Peoples et al, 1995a, Reis et al, 2002, Takahashi et al, 1992, Yinbo et al, 1997, Ying et al, 1992, Zotarelli, 2000; (3) 15 N dilution and abundance techniques (Afza et al, 1987, Alvarez et al, 1995, Alves et al, 2006, Amarger et al, 1979, Bergersen et al, 1989, Bergersen et al, 1992, Boddey et al, 1990, Chapman and Myers, 1987, Coale et al, 1985, Eaglesham et al, 1982a, Eaglesham et al, 1982b, George and Singleton, 1992, Guffy et al, 1989, Hardarson et al, 1984, Hardarson et al, 1989, Kucey et al, 1988a...…”
Section: Data Sourcesmentioning
confidence: 99%
“…Because some studies on N fertilization did not concurrently quantify N 2 fixation and other studies did not evaluate response to N fertilizer when quantifying N 2 fixation, data analyses were performed for two data sub-sets: Data set A was used to examine relationships between N uptake, N 2 fixation and grain yield; Data set B was used to evaluate yield response to fertilizer-N. Data set A comprised 61 studies in which N 2 fixation was quantified. Several different techniques were used: (1) the N difference method (Dashti et al, 1998, Israel and Burton, 1997, Israel and Mikkelsen, 2001, Saxena and Chandel, 1997, Thies et al, 1995, Wagner and Zapata, 1982, Weber, 1966; (2) Ureides determination in the xylem sap (Gan et al, 2002, Guafa et al, 1993, Herridge, 1982, Herridge et al, 1990, Hughes and Herridge, 1989, Hungria et al, 2003, Peoples et al, 1995a, Reis et al, 2002, Takahashi et al, 1992, Yinbo et al, 1997, Ying et al, 1992, Zotarelli, 2000; (3) 15 N dilution and abundance techniques (Afza et al, 1987, Alvarez et al, 1995, Alves et al, 2006, Amarger et al, 1979, Bergersen et al, 1989, Bergersen et al, 1992, Boddey et al, 1990, Chapman and Myers, 1987, Coale et al, 1985, Eaglesham et al, 1982a, Eaglesham et al, 1982b, George and Singleton, 1992, Guffy et al, 1989, Hardarson et al, 1984, Hardarson et al, 1989, Kucey et al, 1988a...…”
Section: Data Sourcesmentioning
confidence: 99%
“…However, a detailed cost benefit analysis would be required to determine whether N fertilizer application is warranted under conditions at Waroona, and, if so, how its effectiveness might be reduced were extensive leaching of applied fertilizer to occur during the crop growth cycle. A major inadequacy of the present approach, and of other similar studies (Amarger et al, 1979;Bergersen et al, 1985;Eaglesham et al, 1982;Kohl et al, 1980), is that no measurements were made of N in root biomass, expecially in relation to the amount of fixed N added by the legume component through decay of roots and nodules at the end of the growing season. For the present purposes, we draw upon the data of an earlier study (Peoples et al, 1983) on potted glasshouse grown cowpea in which it was shown that 12% of the final N of the fully mature plants was recovered from below ground parts.…”
mentioning
confidence: 89%
“…Different techniques such as C 2 H 2 reduction, ureide method (Herridge and Holland, 1987), 15 N dilution (Rennie, 1984;Gao et al, 1987;Guffy et al, 1989), and N-balance studies (Bezdicek et al, 1978;Eaglesham et al, 1982;George et al, 1988) have been used to estimate N 2 fixation by soybean, and the topic has been extensively reviewed by . Of these techniques, the calculation of the N-balance study seems more convenient and can provide more reasonable estimate of N 2 -fixing potential, where N balance is defined as the difference between easily measurable output (N in the exported parts of the plant and residual N in soil at the end of the experiment) and inputs (N applied through fertilizer/manure and depletion of soil N at the end of the experiment).…”
Section: Introductionmentioning
confidence: 99%